Islamic Education from the Perspective of Faith: An Epistemological Study in Learning at School - Rara Bilqis Salsabila; Zumrotul Mukaffa (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Islamic education aims not only to transmit knowledge but also to develop faith and moral character among students. In this context, aqidah plays a fundamental role as a foundation that shapes perspectives on knowledge and the educational process. This study aims to analyze the concept of aqidah in the perspective of Islamic education, explain its role as an epistemological foundation in acquiring knowledge, and examine its implications for students’ ways of thinking in the learning process at madrasahs. This research employs a qualitative approach using library research. Data were collected from books and scholarly articles related to aqidah, Islamic epistemology, and Islamic education. The data were analyzed using content analysis to identify key concepts and thematic relationships systematically. The results indicate that aqidah functions not only as a theological belief but also as an epistemological foundation that determines the sources, methods, and objectives of knowledge in Islamic education. Islamic epistemology integrates revelation, reason, and empirical experience within the framework of tauhid. This approach contributes to the formation of a tawhidic mindset among students, enabling them to think critically, evaluate information selectively, and develop moral and spiritual awareness in the use of knowledge.